2021
DOI: 10.1111/acer.14532
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Clock Analysis in Children With Fetal Alcohol Spectrum Disorder

Abstract: Background Fetal alcohol spectrum disorder (FASD) is characterized by severe clinical impairment, considerable social burden, and high mortality and morbidity, which are due to various malformations, sepsis, and cancer. As >50% of deaths from FASD occur during the first year of life, we hypothesized that there is the acceleration of biological aging in FASD. Several recent studies have established genome‐wide DNA methylation (DNAm) profiles as “epigenetic clocks” that can estimate biological aging, and FASD ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The study identified one of the epigenetic clocks (GrimAge) was significantly associated with FASD in one buccal and both blood datasets, but no significant associations were reported with the other epigenetic clocks. Meta-analysis of datasets by tissue type also reported a significant association between FASD and the GrimAge epigenetic clock in peripheral blood, but no significant association was reported in buccal cells [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study identified one of the epigenetic clocks (GrimAge) was significantly associated with FASD in one buccal and both blood datasets, but no significant associations were reported with the other epigenetic clocks. Meta-analysis of datasets by tissue type also reported a significant association between FASD and the GrimAge epigenetic clock in peripheral blood, but no significant association was reported in buccal cells [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…As detection technology and knowledge of DNA methylation states and cofactors improve, there will be improvements in the precision of biomarker detection. Interestingly, while research has established genome-wide DNA methylation profiles as epigenetic clocks for biological aging, there appears to be accelerated epigenetic aging in individuals with FASD (Okazaki et al, 2020 ).…”
Section: Epigenetics: the Interface Between Genome And Environmentmentioning
confidence: 99%
“…A number of epigenetic clocks have been established based on genome-wide DNA methylation (DNAm) profiles [ 8 13 ]. Such measures have been revealed an association of epigenetic age acceleration with various conditions including Down syndrome [ 14 ], Werner syndrome [ 15 ], Alzheimer’s disease [ 16 ], schizophrenia [ 17 , 18 ], bipolar disorder [ 19 , 20 ], depressive disorder [ 21 , 22 ], suicide [ 23 ], alcohol related disorders [ 24 , 25 ], and posttraumatic stress disorder [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%